Equity Market Anomalies, VIX and Asset Pricing: Trading Strategies for India. Issue 3 (December 2019) - Pandey, Asheesh
In this article we examine five prominent equity anomalies, viz., size, value, profitability, investment and momentum for Indian capital market using data from July 2001 to June 2019. We test the sample anomalies through four prominent factor models and find that all the factor anomalies remain significant for India, however, size and value anomaly provide substantial risk adjusted returns to be exploited by portfolio managers. We further evaluate if the anomalies tend to reverse under different macro-economic uncertainty, which is proxied by VIX. We find barring Size effect none of the anomaly reverses under different macro-economic conditions. We further observe that Fama French three factor model subsumes the majority of the alpha effect, however, none of the factor models fully explain the alphas of sample anomalies. Finally, we find that few of the sample anomalies are countercyclical in nature and thus, provide time diversification opportunity. Profitability-size anomaly provides risk adjusted time diversification opportunity. Our results have significant implications for portfolio managers, policy makers and academia.